2016
DOI: 10.1016/j.cjca.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Values and Preferences of Physicians and Patients With Nonvalvular Atrial Fibrillation Who Receive Oral Anticoagulation Therapy for Stroke Prevention

Abstract: Real-world prescriptions do not reflect reported values, which suggests that other factors influence patient-physician decision-making around OAC therapy. Data on self-reported adherence to OAC therapy and discordance in the use of OACs from prescribed regimens are concerning and warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 16 publications
5
93
2
15
Order By: Relevance
“…This may be because of the once-daily dosing of rivaroxaban and warfarin, which has been shown to be an important consideration for patients and physicians and may be even more important for patients who tend to be less adherent. 7,16 Although dosing regimen may be an important switching consideration, the twice-daily dosing regimen of apixaban did not suggest an effect on adherence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be because of the once-daily dosing of rivaroxaban and warfarin, which has been shown to be an important consideration for patients and physicians and may be even more important for patients who tend to be less adherent. 7,16 Although dosing regimen may be an important switching consideration, the twice-daily dosing regimen of apixaban did not suggest an effect on adherence.…”
Section: Discussionmentioning
confidence: 95%
“…6 Notably, patient and physician preferences typically prefer NOAC profiles compared with warfarin. 7 By late 2013, NOACs as a class had overtaken warfarin as the treatment of choice for anticoagulation, and the market share for NOACs is likely to continue increasing. 1 Studies comparing the adherence of NOACs with warfarin have mostly shown positive results with NOACs and a tremendous burden of discontinuation with warfarin.…”
mentioning
confidence: 99%
“…This may be because of the once daily dosing of rivaroxaban and warfarin, which has been shown to be an important consideration for patients and physicians and may be even more important for patients who tend to be less adherent. 7,16 …”
Section: Discussionmentioning
confidence: 99%
“…6 Notably, patient and physician preferences typically prefer NOAC profiles compared with warfarin. 7 By late 2013, NOACs as a class had overtaken warfarin as the treatment of choice for anticoagulation, and the market share of NOACs has continued to increase. 1 Studies comparing the adherence of NOACs to warfarin have mostly shown positive results with NOACs and a tremendous burden of discontinuation with warfarin.…”
mentioning
confidence: 99%
“…25 Some studies on NOACs showed that single-dose regimen of rivaroxaban was superior to double-dose regimens of apixaban and dabigatran in terms of medication adherence. 19,26 Other studies found no difference in medication adherence between single-and double-dose regimens. 21,27 In our study, double-dose regimen was identified as one of the independent risk factors affecting medication adherence negatively, which is consistent with the hypothesis that fixed-dose combination has better compliance than with a multi-pill regimen.…”
Section: Reasons For Nonadherencementioning
confidence: 99%